Selection of morphological, physiological and biochemical indices: evaluating dwarfing apple interstocks in cold climate zones. Issue 4 (1st October 2016) - Zhao, D; Yuan, J; Xu, K; Cheng, C; Li, H
ABSTRACT: Dwarfing rootstocks are regularly used to cultivate apples in apple-producing countries, including China. Here, we investigated how the use of different dwarfing interstocks affects the growth vigour, morphology, and physical and biochemical indices of Huahong apple saplings. This information was used to elucidate possible mechanisms involved in dwarfing. We found that the degree to which trees were dwarfed differed (63%–83%) with different dwarfing interstocks. Preliminary correlation analysis and factor analysis showed that internode length and the number of root tips represented the main morphological indices for evaluating the dwarfing effects of dwarfing interstocks. In addition, shoot water potential, net photosynthetic rate, indole-3-acetic acid oxidase activity and starch content could be used as physiological and biochemical indices for evaluating the degree of dwarfing. These data provide important insights about the dwarfing mechanisms of dwarfing interstocks to help improve the cultivation methods used for apple production.